Die Epoche Maria Theresias bis zum Ausgleich Österreich-Ungarns aus französischer Perspektive - Pfurtscheller, Stefan (Studien des Interdisziplinären Frankreich-Schwerpunkts der Universität Innsbruck, 2013)
In the present work, the Austrian story is the first time explicitly examined from a French perspective. The author first outlines the relevant directions of the French historical scholarship and subsequently describes important people (Maria Theresa and Joseph II) and events (the creation of the Empire of Austria / abolition of the Holy Roman Empire of the German Nation, Revolution of 1848 and compensation Austria-Hungary).